Structural, Spectral and Thermal Studies of New Bidentate Schiff Base Ligand Type (NN) Derived from Mebendazol and 2-Aminobenzothaizol and its Metal Complexes and Evaluation of their Biological Activity - Shaimaa A. Hassan (Journal of Global Pharma Technology, 2018)
In this study, a new Schiff base [methyl (E)-(6-((benzo[d]thiazol-2-ylimino)(phenyl)methyl)-1H-benzo[d] imidazol-2-yl)carbamate] (L) was prepared and it's complexes with metal ions MII=VO, Mn, Co, Ni, Cu ,Cd,Zn and Hg in ethanol and ace ton with mole ratio (M:L) (1:2). All complexes have general composition [M (L) 2 Cl 2].H2O, [(VO) (L) 2(SO4)].H2O. The ligand and all complexes were characterized by modern spectroscopic (FT-IR, UV_Vis, 1HNMR, 13CNMR, Mass spectroscopy, atomic absorption), along with elemental microanalysis, magnetic susceptibility measurements, thermal analyses, chloride content and molar conductance. In addition to evaluated their biological activity against two type of bacterial and one type fungus. Based on date for all techniques we suggested that all the prepared complexes have octahedral geometry, the value of antibacterial activity of this prepared complexes showed higher inhibition activity compared to the free ligand and starting material.Keywords: 2-Aminobenzothaizol, Mebendazol, Metal complexes, Biological activity.